Preliminary validation of muscle ultrasound in juvenile dermatomyositis (JDM). (16th November 2021) - Mamyrova, Gulnara; McBride, Erica; Yao, Lawrence; Shrader, Joseph A; Jain, Minal; Yao, Jianhua; Curiel, Rodolfo V; Miller, Frederick W; Harris-Love, Michael O; Rider, Lisa G
Abstract: Objective: To compare muscle ultrasound (MUS) parameters in patients with juvenile JDM and healthy controls, and examine their association with JDM disease activity measures and MRI. Methods: MUS of the right mid-rectus femoris was performed in 21 patients with JDM meeting probable or definite Bohan and Peter criteria and 28 demographically matched healthy control subjects. MUS parameters were quantitated by digital image processing and correlated with JDM disease activity measures and semi-quantitative thigh MRI short tau inversion recovery (STIR) and T1 scores. Results: Rectus femoris MUS echogenicity was increased (median 47.8 vs 38.5, P  = 0.002) in patients with JDM compared with controls. Rectus femoris MUS echogenicity correlated with Physician Global Activity (PGA), Manual Muscle Testing (MMT), and Childhood Myositis Assessment Scale (CMAS) (rs 0.4–0.54). Some MUS parameters correlated with functional quantitative measures of muscle strength: resting RF area on MUS strongly correlated with knee extension quantitative muscle testing (rs 0.76), and contracted area correlated with proximal MMT, knee extension quantitative muscle testing, and CMAS (rs 0.71–0.80). MUS echogenicity correlated with both STIR and T1 MRI (rs 0.43), and T1 MRI correlated inversely with RF contracted area (rs -0.49) on MUS. There were differences in pre- and post-exercise vascular power and colour Doppler on MUS in patients with JDM vs controls, with the percentage change of post-exercise vascular power Doppler lower in JDM compared with controls (7.1% vs 100.0%). Conclusions: These data suggest MUS may be a valuable imaging modality to assess JDM disease activity and damage.